2015
DOI: 10.1103/physrevb.91.125203
|View full text |Cite
|
Sign up to set email alerts
|

Electronic stopping power in a narrow band gap semiconductor from first principles

Abstract: The direction and impact parameter dependence of electronic stopping power, along with its velocity threshold behavior, is investigated in a prototypical small-band-gap semiconductor. We calculate the electronic stopping power of H in Ge, a semiconductor with relatively low packing density, using time-evolving time-dependent density-functional theory. The calculations are carried out in channeling conditions with different impact parameters and in different crystal directions for projectile velocities ranging … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
84
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(104 citation statements)
references
References 58 publications
19
84
1
Order By: Relevance
“…This implies that the electronic response along the centroid path is close to the average of the electronic responses in 3C-SiC. In recent RT-TDDFT simulation work by Ullah et al [58] a systematic investigation of impact parameters along channeling paths in bulk cubic Germanium showed that the electronic stopping power can be related to the average density along the trajectory. Our results also support this finding, and they support the notion that the average electron density along the centroid path result in a stopping power that is in good agreement with the ensemble average of random paths.…”
Section: B Examining the Centroid Path Approximationmentioning
confidence: 84%
See 1 more Smart Citation
“…This implies that the electronic response along the centroid path is close to the average of the electronic responses in 3C-SiC. In recent RT-TDDFT simulation work by Ullah et al [58] a systematic investigation of impact parameters along channeling paths in bulk cubic Germanium showed that the electronic stopping power can be related to the average density along the trajectory. Our results also support this finding, and they support the notion that the average electron density along the centroid path result in a stopping power that is in good agreement with the ensemble average of random paths.…”
Section: B Examining the Centroid Path Approximationmentioning
confidence: 84%
“…A future work will focus on exploring the dependence on XC approximation. The XC approximation can also be an important avenue of investigation for the threshold velocity at which the electronic stopping power diminishes [58]. Another more technical source of error is neglecting core electron excitations in our simulations.…”
Section: Discussionmentioning
confidence: 99%
“…This prevents any contribution from nuclear stopping and enables the S e to be directly calculated at a single velocity for each simulation. The electronic stopping is the average gradient of the total energy of the electronic system as a function of the path length of the projectile 25 . The error bars in the S e presented in the figures refer to uncertainty in fitting to the slope.…”
Section: A Simulation Detailsmentioning
confidence: 99%
“…[14], and for a covalent semiconductor like Ge (vth  0.026 a.u.) [37,53]. It remains unclear, whether the lack of correlation between vth and Eg points towards Coulomb collisions with electrons in a strongly perturbed band, towards a different process like the "electron elevator", or towards electron promotion in an atomic collision.…”
Section: Fig 1 Ox Of Vo2 For H Ions (Protons and Deuterons) In Bothmentioning
confidence: 99%